International Comparisons of Clinical Demographics and Outcomes in the International Society of Pediatric Oncology Wilms Tumor 2001 Trial and Study. (10th May 2022) - de Aguirre-Neto, Joaquim Caetano; de Camargo, Beatriz; van Tinteren, Harm; Bergeron, Christophe; Brok, Jesper; Ramírez-Villar, Gema; Verschuur, Arnauld; Furtwängler, Rhoikos; Howell, Lisa; Saunders, Daniel; Olsen, Oystein; Coulomb, Aurore; et al.
Abstract : PURPOSE: International comparisons of patient demographics, tumor characteristics, and survival can shed light on areas for health care system improvement. The International Society of Pediatric Oncology Wilms Tumor 2001 trial/study registered patients through national clinical study groups in Western Europe and Brazil. This retrospective post hoc analysis of the International Society of Pediatric Oncology Wilms Tumor 2001 database aims to make visible and suggest reasons for any variations in outcomes. METHODS: All patients with unilateral Wilms tumor (WT), age > 6 months, treated with preoperative chemotherapy as per protocol, and registered between 2001 and 2011 were eligible. Countries were grouped to give comparable case numbers and geographical representation. Cox univariable and multivariable (MVA) statistics were applied, with the German collaborative group (Gesellschaft für Pädiatrische Onkologie und Hämatologie—Austria, Germany, and Switzerland) as reference for hazard ratios for event-free survival (EFS) and overall survival (OS). RESULTS: A total of 3, 176 eligible patients were registered from 24 countries assigned into six groups. Age and histologic risk group distribution were similar across all groupings. The distribution of WT stage varied by country grouping, with 14.9% (range, 11.1%-18.2%) metastatic at diagnosis. Median follow-up was 78.9 months. For localized WT, 5-year EFS varied from 80% (Brazilian group) to 91% (French group; P < .0001), retaining significance only for Brazil in MVA ( P = .001). Five-year OS varied from 89% (Brazilian group) to 98% (French group; P < .0001). In MVA, only superior OS in France was significant ( P = .001). Five-year EFS/OS for stage IV did not vary significantly. High-risk histology and tumor volume at surgery were significantly associated with increased risk of death in MVA for metastatic disease. CONCLUSION: International benchmarking of survival rates from WT within a large trial/study database has demonstrated statistically significant differences. Clinical interpretation should take account of variation in tumor stage but also treatment factors. Abstract :